ECONOMIC DEVELOPMENT IN THE PERUVIAN DECENTRALIZATION - Andrés Zavala, Abel (2014)
This article appears at the top of the government agenda. In this framework, decisions have been taken and policies that shape significant progress, but still not enough to counter the centralized production pro-file of both platform and the administrative political apparatus. While this mismatch occurs, the chances of meeting goals of equitable and sustainable deve-lopment for the country as a whole will move away.The reform and modernization of the state in general and the executive in particular should consider the inclusion in the government’s organic architecture and mechanisms for management that ensure the best care of citizens’ demands structures. In this regard, they have to be specified more rigorously shared at each level of government (national, regional, provincial, district) and exclusive features, considering that the “regional” designation is a transitional spaces fiction whose coverage alluded finally to departmental or provincial conglomerate united by common expecta-tions and potential.There has been a breakthrough in the transfer of functions or powers from the national government (ministries, decentralized public agencies, special programs) to regional and municipal governments.Decentralization is generally a model of territorial development that meets the legitimate expectations of inclusion, prosperity and access to better opportunities to exercise rights.